Investigation on the material compositions on air cathode in an aluminium- air battery - Koh, Zu Heng (2024)
The development of metal-air batteries has gained intensive focus in recent years. Among the metal-air batteries, the aluminium-air battery is treated as one of the most favoured topics for researchers due to its low cost, high specific capacity and high theoretical energy. To improve the aluminium-air battery performance, there is a lack of information for optimizing the material composition of the air cathode. Thus, this project focuses on the optimization of the material composition of the air cathode by determining the mass ratio of each material. Taguchi Method is utilized to propose the mass ratio of each material for each sample. 5000 series aluminium alloy was selected as the material of metal anode due to its higher corrosion resistance. For the electrolyte, the aqueous KOH electrolyte was chosen as it is capable of providing higher achievable power and larger open circuit potential. The materials used to fabricate the air cathode are carbon black, activated carbon, manganese (IV) oxide, propanol and PTFE. The size of the fabricated prototype was around 3 cm*1.8 cm*4.5 cm. The fabricated samples were tested via discharge test and linear sweep voltammetry test. The results obtained were then analyzed and ranked using Grey Relational Analysis. Several relationships were extracted from the projects to obtain better performance, which is the mass ratio of Carbon Black and Propanol shall be higher and the mass ratio of Activated Carbon and PTFE shall be lower. As a result, the optimized material composition of the powder mixture (Carbon Black, Activated Carbon and Manganese (IV) Oxide), in terms of mass ratio is 9: 1: 2. While the mass ratio of the powder mixture, propanol and PTFE is 1: 3: 1. The optimized aluminium-air battery is capable of providing 1.5 V of plateau voltage, 2.046 Ah/g of specific capacity, 0.137 W of peak power and 0.3247 A of shutdown current which mainly contributed by the effect of optimized air cathode. The high plateau voltage and peak power obtained in the project further indicate the possibility of the subsequent development of air cathode optimization. In addition, the implementation of large-scale prototype will further enlarge the application of the fabricated aluminium-air batteries.